Metrological characterisation of low-cost and wearable sensors for research on healthy buildings in a novel Living Laboratory - Rolle Francesca; Favoino Fabio; Arcamone Giuseppina; Pellegrino Anna; Russo Ramona; Iacomussi Paola; Musacchio Chiara; Bottacin Alberto; Pavarelli Stefano; Prato Andrea; Schiavi Alessandro; Sega Michela (EPJ Web of Conferences)
To achieve the EU targets in terms of ecological transition, and to assure people health, wellbeing and comfort in the indoor environment, research in the building sector plays a fundamental role. In the last decades the energy efficiency and indoor environmental quality (IEQ) of buildings have increased significantly, but a gap between the actual operational performances of sensors and the expected measurement results and still exists. The Italian project “MIRABLE - Measurement Infrastructure for Research on heAlthy and zero energy Buildings in novel Living lab Ecosystems”, carried out in cooperation between the Italian National Metrology Institute, INRiM, and the Polytechnic University of Torino, aims to develop a methodology to reduce this gap by creating and validating a measurement infrastructure for monitoring the multi-domain indoor environmental conditions and the occupants’ interaction in a full scale Living Laboratory (denominated “H-IEQ LL”). The final goal of the research is to support the realisation of healthy and smart buildings and to reduce energy use. Among the activities of the MIRABLE project, the development of methodologies for defining a ground-truth for low-grade and wearable sensors for IEQ measurements in ongoing. After a thorough analysis of the sensors available on the market, and of the best practices to monitor the occupants’ comfort and interaction with buildings, a set of sensors were selected and metrologically characterised for the four domains on interest for the H-IEQ LL: thermal conditions, lighting conditions (spectral distribution included), acoustic conditions and indoor air quality. The monitoring of the response of the occupants to these variables, by means of low-cost sensors mounted on fixed monitoring stations in the LL and of wearable sensors, will allow to evaluate their feedbacks and interaction with the building systems in a dynamic mode. An overview of the results obtained from the metrological characterisation of IEQ sensors carried out at INRiM, and the preliminary calibration for some of the measured variables (e.g. temperature, sound pressure, CO2 level, lighting), are presented in this work. The sensors will be installed in the LL, to create a sensor network for multi-domain monitoring of the physical environment and some wearable sensors will be used to monitor the occupant related quantities in a well-controlled environment. A methodology for the sensors in situ use, data collection and periodic calibration is also under definition.